Hikayat Prang Sabi: Acehnese Jawi as a Medium of Successful Da’wa - Syukri Rizki (Proceedings of International Conference on Da'wa and Communication, 2019)
Besides serving as a means of entertainment, a hikayat in Aceh plays a salient role when it comes to inculcating the Islamic values to perform jihad. An epic Hikayat Prang Sabi – which is written in Acehnese Jawi – is evident to spur the Acehnese people to struggle against the Dutch invaders during the Aceh War. Numerous studies have been conducted on this hikayat to scrutinize the striking motivation it harbors. Noticeably, the hikayat is proof that Acehnese Jawi became an effective medium in successfully transmitting the da’wa to defend land and soul. However, the orthography, unlike Malay Jawi, now suffers from the lack of attention in terms of its writing system. Therefore, it is imperative to study how the orthography is employed so that it had such sheer readability in communicating the divine message. For this reason, this study attempts to unravel the Jawi writing system employed by the author in writing the hikayat. Content analysis is conducted on the script of the hikayat which is the subject of this study. It is found that the hikayat is written in various Acehnese dialects, which then affect the Jawi spelling. The Acehnese Jawi in the hikayat does share the same spelling in some words with Malay Jawi even though pronounced differently. A plethora of Arabic loanwords maintains their original spellings in Acehnese Jawi while some others are customized to suit the progressive change of local pronunciation and due to the attachment of prefixes and suffixes.